การศึกษาการแปลงหลักสูตรการศึกษาขั้นพื้นฐาน พุทธศักราช 2544 ไปสู่การสอนของครูในโรงเรียนใช้เทคโนโลยีสารสนเทศและการสื่อสารเพื่อพัฒนาการเรียนรู้ - ปิยวัติ ธรรมพักตรกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
Studies the operation and problems in transferring the basic education curriculum B.E. 2544 to instruction of teachers in the Information and Communication Technology (ICT) utilization for learning development schools. Research samples are 6 school that utilized ICT for learning development. Sources of data consist of teachers in elementary and secondary levels in each learning subject group; cheifs of student activity group. Research tool has used the semi-structured interview forms. Statistical analysis has been used for frequency distribution and percentage. Presentation of the results are in table, with description. The results of the research study found that in the operation of transferring the basic education curriculum to instruction, the teachers interpreted the curriculum aims, set up lesson unit, lesson plan and learning materails. Chiefs of student activity group set up student activities through bringing in ICT for typing documents, filing data search related to the basic education curriculum B.E. 2544, including learning activties done by other learning materials and learning resources. The ICT is also used for presenting data and document for the meeting on transferring curriculum to instruction. In preparation of lesson plans, The teachers define the learning objectives, activities, learning materials, learning resources and learning evaluation. Learners will be instructed to use computer and internet to gain knowledge and data search. They were trained in drafting, presenting performance reports and utilizing computer in examinations. In addition, Learners will also be assigned to use television and radio programs as media of learning and information search. Learners will be realized the contribution of ICT utilization for learning. On the part of cheifs of student activity group, they will assign learners to use computer and internet for data information searching. Learners will also assigned to use electronic tools such as radio, VDO, cassettes and VDO recorders for each student activity group. Problems found in transferring curriculum to instruction of teachers are as follows: the teachers are lack of knowledge and understanding in transferring the basic education curriculum B.E. 2544 to instruction. They also have insuffcient skills in using the ICT. In addition, they could not gain adequate ability to set up lesson plan which relates to ICT. However, as for the cheifs of student activity group, they have not found any problems in setting up student activity group.